Strategies of Modeling, Monitoring, Professional Dialogue and the Effectiveness of Principal Leadership to Teachers During the Pandemic of Covid-19 - Pramono, Pramono; Arafik, Muh; Nurabadi, Ahmad; Triwiyanto, Teguh (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
The purpose of this study was to determine the strategies of modeling, monitoring, professional dialogue, and the effectiveness of the principal’s learning leadership to teachers during the novel coronavirus disease (COVID-19) pandemic. A quantitative approach was used in this research. The population of this research is the principals of public elementary schools in Malang City, Malang Regency, and Batu City, East Java Province, Indonesia, amounting to 1,323. The sample selection used was random sampling, with a total of 290 people or 22 percent of the population. Data analysis used path coefficient analysis. The results showed that strategies of modeling, monitoring, and professional dialogue affected the effectiveness of learning leadership during the COVID-19 pandemic.